Appearance of textures with a c-axis parallel to the extrusion direction in Mg alloys. (15th March 2022) - Wang, Jun; Ferdowsi, Mahmoud Reza Ghandehari; Kada, Sitarama Raju; Babaniaris, Steven; Hutchinson, Bevis; Lynch, Peter A; Barnett, Matthew R.
Abstract: The appearance of an unusual texture with the crystallographic c-axis parallel to the extrusion direction ('C-texture') occurs in bands in extruded and fully recrystallized Mg-6.5Zn alloy. This texture was previously only reported in rare-earth-containing Mg alloys. Based on our results and the available literature, it seems that this texture requires heavy alloying, and it is not linked exclusively to the presence of second phase particles. Moreover, it appears to be associated with higher extrusion ratios. Also, the starting texture seems not essential for its formation. The most likely mechanism would be the promoted pyramidal slip stimulated by high solute levels that provides the necessary lattice rotation, along with the easy activation of prismatic slip. Graphical abstract: Image, graphical abstract